Chemical composition of skeletal muscle - Abrão Anghihan; Francisco B. De Jorge; Julinho Aisen (Arquivos de Neuro-Psiquiatria)
The present paper aims to presents standard values for the contents of water, sodium, potassium, calcium, magnesium, phosphorus, copper and iron in muscles (tibialis anterior, deltoid and pectoralis major) in individuals without any neurological conditions. This study shall constitute the basis for the interpretation of other data, still being gathered, relating these normal values with those obtained for muscles under pathological conditions.